Analysis of Demographic and Causal Factors of Maxillofacial Injuries in Polytrauma Patients: A Study from a Tertiary Care Hospital of Bangladesh - Dey, Audity; Chowdhury, Akram Pervez; Khan, Mohammad Azom; Zahur, Tamanna; Barua, Monoj Kumar (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Maxillofacial trauma is highly prevalent and has a complex etiology that varies globally due to social, environmental, and cultural factors. The present study was aimed to analyze the demographic characteristics and causes of the maxillofacial injuriesin polytrauma patients from a tertiary care hospital of Bangladesh. Materials and methods: This cross-sectional observational study was carried out in Chittagong Medical College Hospital, Chattogram, upon purposively selected 102 patients for six-month period from May 2021. Data were collected by a pre-tested structured case record form. Chisquare tests were used to perform intergroup and categorical comparisons as appropriate. p value < 0.05 was considered to represent a statistically significant difference. Results: The age of the respondents ranged from 4-68 years with the mean ± SD was 27.1 ±13.5 years. The age group 20-29 years accounted for the largest subgroup in both sexes. Road traffic accidents were the most common form of etiology for trauma (43.1%) followed by accidental falls (31.4%). Single maxillofacial fracture wasobserved in 58.8% of the cases while multiple fractures were observed in 41.2%of the patients. Males (46.3%) in this study were significantly (p=0.032) more likely to sustain multiple maxillofacial fractures compared to females (20.0%). Conclusion: Reducing the frequency and severity of this type of injuries in Bangladesh requires increasing public awareness, enhancing trauma management, directing preventive initiatives, and shaping public health policy. JCMCTA 2025 ; 36 (1) : 154-158